Analisis Kritik Objektif dan Mimetik Pada Novel Selamat Tinggal Karya Tere Liye dan Implementasinya Terhadap Pembelajaran Sastra - Fauzia, Regina (Jurnal Artikula, 2025)
This study aims to analyze the intrinsic and extrinsic elements of Tere Liye's novel "Selamat Tinggal" (Goodbye) and how it can be implemented as teaching material in high school. The objective approach focuses on the novel's intrinsic elements (theme, plot, characterization, setting, point of view, style, and moral), while the mimetic approach focuses on the novel's extrinsic elements (moral and religious values, social and cultural values) based on Abrams' theory (in Aminuddin 2015). The method used in this study is descriptive qualitative. The research data consists of dialogues sourced from the novel. Data collection used listening and note-taking techniques. The steps in data analysis included reading the entire novel, classifying the data, interpreting the data, and then identifying data related to the novel's intrinsic and extrinsic elements, including moral, religious, social, and cultural aspects. Based on the analysis, a total of 29 data points were found, 20 of which fall within the intrinsic elements of the novel using the objective approach, and 9 of which fall within the extrinsic elements using the mimetic approach. The research results can be implemented as teaching materials for critical analysis and assessment of literary works with the aim of understanding, appreciating, and providing a deeper understanding of literary works. The context of moral, religious, and socio-cultural values is expected to broaden the horizons of all educational elements to support the success and progress of education in line with intellectual intelligence and moral perfection, because learning is essentially a process of behavioral change that underlies literary criticism in Literature learning, particularly in phase F (grades XI and XII) of high school